Pengetahuan Keluarga Tentang Pencegahan Penyakit Covid-19 di Kelurahan Penaraga Wilayah Kerja Puskesmas Pena Nae - Arismansyah Arismansyah; Arisa Putra; Dahlan Dahlan; Rini Hendari; Kurniadi Kurniadi (Bima Nursing Journal, 2022)
Covid-19 is currently a serious world problem with the number of cases increasing every day. Attacks everyone regardless of age or gender. In the province of West Nusa Tenggara, patients with the corona virus reached 9,698 patients, 8,338 recovered, and 404 patients died (Rikesda Prov.NTB, 2021). In Bima City, there were 1106 COVID-19 cases. Many residents did not know about COVID-19 and did not comply with the COVID-19 prevention protocol in the form of washing hands with soap and running water, wearing masks, maintaining distance and avoiding crowds by staying at home. Preventive action is the key to implementation in health and community services (PERKESMAS). Prevention steps in the community are to wash hands with hand sanitizer, wear masks, and maintain a distance (at least 1 meter) from other people. This study aims to describe the family's knowledge about the prevention of COVID-19 in the Penaraga Village, the working area of the Pena Na'e Health Center. using descriptive analytic method with cross sectional design. The population in this study were all families in Penaraga Village, Pena Nae Health Center working area as many as 214. The sample in this study was families in Penaraga village, totaling 25 samples. sample among the population in accordance with the wishes of the researcher. The type of research instrument that can be used in this study is a questionnaire with 10 question items. Results. The data obtained from family knowledge about COVID-19 prevention in Penaraga Village, Pena Nae Health Center, Bima City, the majority of respondents were knowledgeable enough, namely 13 respondents with a percentage (52%), good knowledge as many as 7 with a percentage (28%), and then respondents who had less knowledge as many as 5 respondents with a percentage (20%)